Information exchange in retail markets with uncertainty about downstream costs - Daniel Herold (Philipps-University Marburg, School of Business and Economics, 2017)
An information exchange between two producers selling independent products to the same retailer can have ambiguous effects on market efficiency and surplus. When a retailer's costs are unobservable the producers may have an incentive to communicate about their negotiations with that retailer. If each producer is allowed to place one offer the producers will have no incentive to exchange information. However, the retailer may communicate that he refused the first offer to the other firm which subsequently might place a lower offer. When one firm is allowed to place a second offer, two equilibria involve communication between the producers. In a separating equilibrium an information exchange ensures that agreement will always be found. In a hybrid equilibrium, the likelihood that agreement is found is less likely.
Keywords: L41; L42; L13; 330